#TITLE_ALTERNATIVE# - (NIM. 90212004) ;Pembimbing Dr. Siti Nurul Khotimah, Wahyu Hidayat, M.Si, NURJANAH
The results of a survey by a senior high school in Semarang have shown 88% of its students have difficulties in learning physics. These difficulties occur due to inappropriateness models, methods, and instructional media used by teachers. One way to solve this problem can be done by creating mobile learning.